ROLE OF SERUM LIPIDS IN GALLSTONE PATHOGENESIS: A CASE–CONTROL STUDY FROM PUNJAB - Kaur, Apinder; Kaur, Amandeep; Kaur, Satbir (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Pathogenesis of gallstone (GS) disease is multifactorial, involving both genetic and environmental factors. The main pathogenic factor responsible for the hypersecretion of cholesterol into bile is the impaired lipid metabolism, which actually reflects the likelihood of GS formation. The study aims to determine the significance of serum lipids in the etiology of GS disease and to identify the possible confounding effects of age, gender, and body mass index (BMI) on GS disease. Methods: A case–control study was conducted on 97 ultrasonically confirmed GS cases and 92 healthy controls which were further divided on the basis of gender, age group (≥40 and <40 (y)), BMI (obese and non-obese), and number of stones (single and multiple). The serum lipid parameters were estimated using the enzymatic kit assay. The statistical analysis of the lipid parameters in relation to age, gender, obesity, and stone number was done using the Student's t-test, Chi-square test, and Mann–Whitney U-test. p<0.05 was considered statistically significant. Results: The mean serum total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) were significantly higher in cases as compared to controls (p=0.0001 [95% confidence interval [CI]: 33.3–61.2] and p=0.0001 [95% CI: 36.6–64.2], respectively). The serum high-density lipoprotein cholesterol (HDL-C) level was non-significantly lower in GS patients as compared to controls (p=0.4). Obese female patients of age group ≥40 (y) had an abnormal lipid profile with a significant rise in mean TC, LDL-C, and triglycerides (TG) (p<0.05) and were at higher risk of developing the GS disease as compared to controls. However, no probable effect of abnormal lipid profile, age, gender, and BMI on increasing the number of stones was found (p>0.05). Conclusion: Abnormal lipid parameters, especially high TC and LDL-C, were found to be significantly associated with GS disease. Increased age, obesity, and female gender along with dyslipidemia altogether elevate the risk of formation of GS. The formation of single/multiple stones was not influenced by the abnormal lipid profile, age, gender, and BMI.